Analisis Pengaruh Infrastruktur terhadap Ketimpangan Pembangunan Ekonomi Wilayah di Provinsi Aceh - Muhammad Furqan; Safuridar Safuridar; Puti Andiny (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2026)
This study aims to analyze the influence of road infrastructure, education level, and electricity consumption on regional economic development inequality in Aceh Province. Development inequality remains a major challenge despite Aceh’s relatively low Gini Ratio compared to other provinces in Indonesia. Differences in infrastructure quality among districts and municipalities are expected to affect income distribution and community welfare. This study employs a quantitative approach using secondary data obtained from the Central Bureau of Statistics of Aceh Province and the Aceh Regional Development Planning Agency for the 2008–2023 period, covering 23 districts and municipalities. Multiple linear regression analysis with EViews 13 is applied to examine the relationships among variables. The dependent variable is economic development inequality, measured by the Gini Ratio, while the independent variables include road infrastructure, education level, and electricity consumption. The findings are expected to provide valuable policy recommendations for promoting equitable regional development and sustainable economic growth.